(untitled) (Patrimônio e Memória, 2018)
The city of Recife, in the Northeast of Brazil, cut by rivers and bathed by the sea, has in its waters its main characteristic. Among its rivers, the Capibaribe stands out for the route, its historical importance, having been in the past one of the main axes of occupation of the territory. In its course, different units of landscape constitute its physiognomy that extends beyond the channel, soaking and giving identity to the city. This landscape of memory was the defining feature of the project Parque Capibaribe: Caminho das Capivaras (Capibaribe Park: The Capybaras Path), under development by InCiti – Pesquisa e Inovação para as Cidades da Universidade Federal de Pernambuco (Research and Innovation for the Cities of the Federal University of Pernambuco) –, in partnership with the City Hall of Recife. If a landscape project requires perception, analysis and appropriation of values, redesigning the Capibaribe as a park demonstrated the strength that this water line imposes as landscape. It is about this previous pulsar and its conceptual refutation in the project that it is proposed to discuss.